Upgrading the Capacity of Local Community and Tourism Branding in Pagar Jaya Village - Rahman, Yudha; Kurnianingsih, Nela Agustin; Putri, Marsista Buana; Wiguna, Anindita Nanda; Rahmadinanti, Nabila Azahara; Soﬁani, Nita; Raihan, Ahmad; Ramadhan, Khalid Ahmad; Falyajaya, Fatthah Ikhwan (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Pagar Jaya Village is a coastal area at the southernmost tip of Sumatra Island and isolated in Punduh Pidada District, Pesawaran Regency, Lampung becoming one of the tourism villages in Lampung that has two main problems poor accessibility and low capacity of the community. As a result of this problem, the "KITA PAGAR JAYA" program has successfully enhanced the community’s capacity in tourism, particularly in the area of tourism branding. This program itself is implemented with Sadar Wisata and Sapta Pesona approaches. It was developed on 4 stages, ﬁrst stage is potential and problem identiﬁcation, second stage is delivering material about tourism management, the third is about MSMEs and branding knowledge, and the last stage is about evaluation of tourism management to develop sustainable system in Pagar Jaya Tourism. The implication of this program is to enhance the local community’s capacity to manage tourism by focusing on Sadar Wisata, Sapta Pesona, and disaster management. As a result, more community members are joining the Pagar Jaya Village Tourism Awareness Group and MSMEs to help with tourism management. The program also includes creating promotional materials like pocketbooks, tourism videos, and social media campaigns to enhance the branding of Pagar Jaya Village.